Relationships among gene expression and anthocyanin composition of malbec grapevine clones - Muñoz, Claudio Javier (2014)
Anthocyanin profiles are commonly used for grapevine cultivar identification because it is currently accepted that this trait is closely related to their genetic characteristics. Nevertheless, the extent of the variation for the anthocyanin profiles among clones of the same cultivar has not yet been studied in depth. The relative concentration of anthocyanins of 131 Malbec clones grown in the same vineyard was investigated by HPLC-DAD and the use of comprehensive statistic procedures. Complementarily, the expression level of structural and regulatory genes was studied via real time polymerase chain reaction. Significant variation was identified among the profiles of the clones, mainly due to variations in the amounts of malvidin derivatives. Finally, the differential expression in F3′5′H, OMT1 and AM2 genes seems to be related to the malvidin content variation. This work shows the existence of variation for the anthocyanin profiles among clones from the same grapevine cultivar and the putative involvement of genes related to hydroxylation, methylation, and transport of anthocyanins on the basis of such variation.